Вераны вуиз вакыт: кылбуръёс / Александр Белоногов - Белоногов Александр Егорович (Удмуртия, 1988)
Экземпляры: АБ (20140430) / Инвентарный номер: 16314 / Сис.шифр: С(Удм) / Авт.знак: Б 43 / ГРНТИ: 17.82.10 / ББК: 84(Удм)